The Artikel HUBUNGAN ANTARA INTENSITAS MEDIA SOSIAL DENGAN ETIKA KOMUNIKASI SISWA SMP N 2 PALANGKA RAYA TAHUN AJARAN 2021/2022: HUBUNGAN ANTARA INTENSITAS MEDIA SOSIAL DENGAN ETIKA KOMUNIKASI SISWA SMP N 2 PALANGKA RAYA TAHUN AJARAN 2021/2022 - Lois Hutajulu; Romiaty Romiaty (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Palangka Raya, 2022)
Abstract This study was conducted to determine the relationship between the intensity of the use of social media with students' communication ethics. This research is a correlation study, with a sample of 48 people. The main data collection technique in this study used a questionnaire on the use of social media and communication ethics to determine whether there was a relationship between the use of social media and students' communication ethics. From the results of research analysis using product moment correlation obtained r count of -0.018. Looking at the 5% significance level in the product moment r table with dk = n-2 = 48-2=46, it is obtained a value of 0.291 at a significance level of 5%. Thus, the value of r arithmetic < r table with a level of sig (2-tailed) is 0.905 more than 0.05. And it can be interpreted with the degree of relationship that the relationship between the intensity of social media use and communication ethics is low, which lies in the coefficient interval of 0.00 – 0.199. With the conclusion that there is a relationship between the intensity of the use of social media on communication ethics. Indeed, in the results there is a relationship, but the relationship is negative and less significant. Where the higher the intensity of using social media, the lower the communication ethics of SMP N 2 Palangka Raya students.